KIMIA DARAH (SGPT, SGOT, BUN DAN KREATININ) KUDA THOROUGHBRED YANG DIPELIHARA DI DAERAH ISTIMEWA YOGYAKARTA DAN JAWA TENGAH - , WIDIAH EKA PUTRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia's horse population has been decreasing from year to year. In 2002 approximately 446,000 horses , while in 2006 decreased to 329 864 horses. This phenomenon illustrates that the horses in Indonesia are at risk of extinction. One of the factor causing the extinction of the horses we the disease in horses. In connection with the issue needs to be taken for the prevention of disease by knowing the chemical profile of the horse blood . The purpose of this study was to evaluate normal standard blood chemistry including Serum Glutamic Piruvic Transaminase (SGPT) , Serum Glutamic Oxaloacetic transaminase (SGOT) , Blood Urea Nitrogen (BUN) and creatinine in thoroughbred horses in DIY and Central Java. The results of this study could be used as references of veterinary and veerinary clinical in disease to control the disease quickly and accurately . Healthy thoroughbred horses from Yogyakarta and Central Java were used. A total of 2 pony came from stable in Yogyakarta and 5 come from Central Java. Sex fillies by 2 and 5 stallions, horses ranged from 2.5 to 6 years of age. The results showed that the activity value of SGPT 8,35-13,32 IU/L, SGOT 206,4- 360,6 IU/L, BUN 10,83-19,19 mg/dL and Creatinine 1,23-1,99 mg/dL.